Green Building Certification as a Policy to Promote Green-Building - A Study of Singapore, Taiwan, Australia, UK, US and Lessons for Vietnam - Pham, Thuy Loan; Nguyen, Tat Thang (International Journal of Sustainable Construction Engineering and Technology, 2021)
To cope with global environmental crisis and warming, Green Bbuilding (GB) has become a world-wide common trend in construction industries and each country has adopted different policies, programs, strategies to promote GBs in accordance to its owned conditions and context. This paper looks at GB certification from the len of a GB promotion policy, therefore, it concerns about the governmenntsâ€™ points of view and actions related to GB cerfitication. The paper summarizes a study of GB certification policies in five countries: Singapore, Taiwan, Australia, UK and US; then overviews current state of GB development in Vietnam, reviews current policy context and analyzes roles of different stakeholders in the market. Through the understanding of the local context, the lesson learnt from the internationally experiences, this paper suggests a policy orientation for excelarating GB development in Vietnam.